Online Correction of the Dynamic Errors in a Stored Overpressure Measurement System - Wei Wang; Zhijie Zhang (Universitas Ahmad Dahlan, 2015)
The problem encountered in sharp shock testing as a result of inadequate bandwidth must be addressed to obtain an accurate overpressure peak value when measuring the steep signals of shockwaves during explosions. A dynamic compensator can effectively amend the dynamic errors caused by sensor system characteristics; thus, a dynamic compensation method based on improved particle swarm optimization (PSO) algorithm is proposed in this paper. This method can effectively overcome the influence of the initial value derived with PSO algorithm on compensator index. The distributed algorithm is introduced into the hardware structure design of the dynamic compensator to facilitate the application of an optimized compensator to real-time online measurement. This integration realizes the high-speed parallel of the dynamic compensator of the sensor with field-programmable gate array. Experimental results show that a high-speed parallel dynamic compensator can amend the dynamic errors in a sensor accurately and in a timely manner.